2009
DOI: 10.1111/j.1365-2834.2008.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing shaping and influencing health and social care policy

Abstract: All leaders and other stakeholders require to play their part in considering how the actions set out in this article can be taken forward and how gaps such as education, fellowship experience and media engagement can be addressed in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 26 publications
0
41
0
2
Order By: Relevance
“…Our findings also support the work of Oliver, Gallo, Griffin, White, and Fitzpatrick, [48] who found that NMs' active participation in decision-making significantly increased job satisfaction and enhanced quality of care. Similar to Fyffe [49] and Paliadelis, [17] our findings demonstrated the importance of developing a political sense and understanding the strategic organizational power of nursing leadership. In agreement with these authors, we also found that the awareness of NMs' influence over issues and their ability to recognize who one's allies within the organization are, can contribute to provide them with a sense of autonomy, utility, and control over their administrative practice.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Our findings also support the work of Oliver, Gallo, Griffin, White, and Fitzpatrick, [48] who found that NMs' active participation in decision-making significantly increased job satisfaction and enhanced quality of care. Similar to Fyffe [49] and Paliadelis, [17] our findings demonstrated the importance of developing a political sense and understanding the strategic organizational power of nursing leadership. In agreement with these authors, we also found that the awareness of NMs' influence over issues and their ability to recognize who one's allies within the organization are, can contribute to provide them with a sense of autonomy, utility, and control over their administrative practice.…”
Section: Discussionmentioning
confidence: 49%
“…To our knowledge, there is an urgent need to invest economically in creating a humanistic work environment that facilitates the adaptation of NMs and their personal and professional development as they transition to management practices based on caring attitudes and values (e.g., compassion, gentleness, mutual respect). [49,50,[52][53][54][55][56][57] As professionals, nurse executives and administrators can make caring the norm and can help attain the dual goal of fiscal responsibility and optimal patient care. [58] Some of our findings enrich the existing knowledge found in the literature, while innovative results add to the body of knowledge related to the advancement of nursing management.…”
Section: Implications For Nursing Managementmentioning
confidence: 99%
“…Nurse educators need to further explore why this is the case in order to ensure that nurses of the future are aware of their role and responsibilities in this area and that they have the skills to work effectively to influence and build healthy policy. Two recently published discussion papers highlight the role of nursing education to prepare nurses for participation in the political process, especially needed to reduce health inequalities in the community (Carnegie & Kiger, 2009, Fyffe, 2009. Nurses have unique knowledge about the health and well being of the communities in which they live and work and this knowledge and experience needs to be harnessed to inform effective policy and practice development.…”
Section: Discussionmentioning
confidence: 99%
“…In another study on nurses' performance development strategies by Canadian Nurses Association; also one of the most effective strategies is considering the groups directly affected by underlying policies. Nurses' participation in the national media is another facilitator that has been supported in some studies conducted in the field of nurses' participation in policy making (Fyffe 2009). The third main category in this study is conditions governing the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile because of less notification to nursing profession in local and national policies, existing policies often not cover high quality nursing care and related issues to nursing (Hewison 2008). Thus, if nurse leaders want policies to be reflection of nursing values and issues, they have to effect on policies (Fyffe 2009). In 2009, when Iran's macro plan of health polices entitled Iran Comprehensive Health Map, had been developed by health politicians as authors, they had requested for the opinions and advises of many health disciplines include nursing, but just few nurse leaders had involved with declaring their opinions.…”
Section: Introductionmentioning
confidence: 99%